ALTERNATIF DESAIN STRUKTUR JEMBATAN MENGGUNAKAN BAJA TIPE BOWSTRING TRUSS PADA JEMBATAN NIOGA KABUPATEN PUNCAKJAYA WAMENA - Nova Verocha; Warsito Warsito; Azizah Rachmawati (Jurnal Rekayasa Sipil, 2020)
Puncak Jaya Regency is a regency located in the central mountainous region of Papua Island and is included in thePapua Province region. Geographically located at position 137 ° 15 '- 138 ° 15' East Longitude and 2 ° 0 '- 3 ° 0' SouthLatitude. In the Usulimo - Karubaga - Mulia section in Puncakjaya Regency there is an area separated by a river. Thegovernment connects the area with the Nioga bridge. At present the bridge uses a Truss type steel frame construction.The bridge is a national transportation system that has an important role especially in supporting the economic, socialand cultural and environmental fields. The purpose of this planning study is to plan the structure of a bridge frame usinga Bowstring Type steel frame with a span of 40 meters and a width of 9 meters. In Nioga bridge planning using theLoad and Resistance Factor Design method and for the analysis of bridge structure modeling using the STAAD Proprogram. On this bridge it is planned to use steel profiles WF 400x200x8x13 for longitudinal girder, WF900x300x16x28 for transverse girder, WF 388x402x15x15 for lower main girder and curved main girder, LD150.150.19 for upper, middle and lower wind ties. The dimensions of elastomeric pads are 60 cm long, 60 cm wide, and16.2 cm high. The foundation used is the pile foundation with a diameter of 30 cm with a number of 10 poles at a depthof 14m.